Pelargonidin reduces the TPA induced transformation of mouse epidermal cells –potential involvement of Nrf2 promoter demethylation. (25th August 2019) - Li, Shanyi; Li, Wenji; Wang, Chao; Wu, Renyi; Yin, Ran; Kuo, Hsiao-Chen; Wang, Lujing; Kong, Ah-Ng
Abstract: Pelargonidin, a well-known natural anthocyanidin found in berries strawberries, blueberries, red radishes and other natural foods, has been found to possess health beneficial effects including anti-cancer effect. Herein, we investigated the effect of pelargonidin on cellular transformation in mouse skin epidermal JB6 (JB6 P+) cells induced by tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA). Pelargonidin treatment significantly decreased colony formation and suppressed cell viability of JB6 P+ cells. Pelargonidin also induced the anti-oxidant response element (ARE)-luciferase activation in HepG2-C8 cells overexpressing the ARE-luciferase reporter. Knockdown of nuclear factor E2-related factor 2 (Nrf2) in shNrf2 JB6 P+ cells enhanced TPA-induced colony formation and attenuated pelargonidin's blocking effect. Pelargonidin reduced the protein levels of genes encoding methyltransferases (DNMTs) and histone deacetylases (HDACs). Importantly, pelargonidin decreased the DNA methylation in the Nrf2 promoter region of JB6 P+ cells and increased Nrf2 downstream target genes expression, such as NAD(P)H/quinone oxidoreductase 1 (NQO1) and heme oxygenase-1 (HO-1), involved in cellular protection. In summary, our results showed that pelargonidin blocks TPA-induced cell transformation. The possible molecular mechanisms of its potential anti-cancer effects against neoplastic transformation may be attributed to its activation of Nrf2-ARE signaling pathway and its cytoprotective effect. Highlights: Anthocyanin pelargonidin attenuates colony formation of JB6 mouse epidermal cells. Pelargonidin transcriptionally activates the antioxidant response element (ARE). Pelargonidin enhances Nrf2-mediated antioxidant gene expression. Knockdown of Nrf2 attenuates blocking effect of pelargonidin on colony formation. Pelargonidin epigenetically decreases the DNA CpG methylation of Nrf2 promoter.